Manajemen Kepemimpinan Madrasah Dalam Pemulihan Pembelajaran Pasca Pandemi Covid-19 - Siswadi Siswadi; Ahmad Mukhlasin; Rahman Afandi; Mukroji Mukroji (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2022)
This study aims to analyze madrasa leadership management in post-COVID-19 learning recovery. The pandemic has caused various challenges in education, including learning loss, digital inequality, and declining quality of instructional interaction. Therefore, adaptive and innovative leadership is required to manage the recovery process effectively. This study employs a qualitative approach using a library research method, with data collected from relevant academic literature published between 2018 and 2022. The findings indicate that madrasa leadership management in learning recovery is implemented through strategies such as identifying learning loss, strengthening adaptive curricula, improving teacher competencies, and optimizing the use of educational technology. In addition, collaborative leadership and psychosocial approaches play a crucial role in supporting successful learning recovery. Thus, effective madrasa leadership can act as a transformative agent in improving educational quality and building a more resilient learning system in the post-pandemic era.